Energy level structure of the ground configuration in the Er3+ free ion. (30th April 2015) - Radžiūtė, L; Kato, D; Gaigalas, G; Jönsson, P; Rynkun, P; Jonauskas, V; Kučas, S
Abstract: Energy levels of the ground configuration [Xe]4f 11 in the Er 3+ ion are reported from relativistic configuration interaction calculations. Calculations are performed using the relativistic atomic structure package GRASP2K, which implements the multiconfiguration Dirac–Hartree–Fock method. The Breit transverse interaction and leading QED effects are included as perturbations. The final energies of 41 levels are compared with results from experiment and semi-empirical methods.